RELATIONSHIP BETWEEN KNOWLEDGE AND ORAL HYGIENE ON PERIODONTAL HEALTH STATUS OF THE ELDERLY AT WORKING AREA OF KEDUNGMUNDU PUBLIC HELTH CENTER - Sakinatina, Sintok Nabila; Hartiti, Tri; Failasufa, Hayyu; Arimbi, Arimbi (Faculty of Dentistry, Universitas Islam Sultan Agung, 2025)
ABSTRACT Background: Periodontal disease is an unbalanced oral hygiene and host and can cause chronic inflammatory manifestations in the tissues around the teeth, which is a serious problem in most elderly people. Knowledge about the health of the oral cavity of the elderly is a factor that can affect dental and oral hygiene, where a person with an elderly age has a higher risk of suffering from periodontal disease caused by the aging process. This study aim to determine the relationship between knowledge and oral hygiene on periodontal health status of the elderly at working area of Kedungmundu Public Health Center.Method: This research using observasional analytic with cross-sectional and sample selection using cluster sampling with a total number of samples of 100 people. Statistical analysis uses the Spearman correlation test.Result: The results of the Spearman Rank Correlation statistical test were p-value was 0.005 or there was a relationship between knowledge and oral hygiene and periodontal health status in the elderly.Conclusion: It was concluded that there is a significant relationship between oral hygiene knowledge and hygiene and the periodontal health status of the elderly in the working area of the Kedungmundu Health Center.